THE CHEMICAL COMPOSITION OF DRIED BROWN SEAWEED (Sargassum plagyophyllum) - Putri, Fatma Eka; Diharmi, Andarini; Karnila, Rahman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT Seaweed is a plant-like macroalgae whose habitat is attached to rocks in the coastal areas of Indonesia. Seaweed has the potential as a food ingredient that is rich in nutritional value. Seaweed consists of several classes, namely red seaweed (Rhodophyceae), green (Chlorophyceae) and brown (Phaeophyceae). S. plagiophyllum is a species of brown seaweed with high nutritional value. This study aimed to determine the chemical composition of brown seaweed S. plagyophyllum. The research method used is experimental by conducting a series of experiments. The treatment used was to make S. plagiophyllum seaweed flour before being analyzed. This study consisted of two stages, namely: 1) Sample preparation, 2) Analysis of the chemical composition of S. plagyophyllum flour consisting of moisture, ash, protein, fat and carbohydrate content (by different). The results showed that dried S. plagiophyllum showed that the moisture content, ash, protein, fat, and carbohydrates were 14.50% (ww), 14.70% (dw), protein 9.17% (dw), 2.79% fat (dw), and 58.84% carbohydrates (dw). The highest chemical composition is carbohydrates (58.84% bk) and the lowest is fat (2.79% (wk). Keywords: carbohydrate, chemical composition, seaweed